Nanofósseis calcários do cretáceo na Bacia de Pelotas, RS : infêrencias bioestratigráficas e paleoecológicas - Guerra, Rodrigo do Monte (Universidade do Vale do Rio dos Sinos, 2011)
This study reports biostratigraphic and paleoecologic inferences based on the distribution of calcareous nannofossils in three wells drilled in Pelotas Basin continental shelf, southern Brazil. The first biostratigraphic study in the basin comes from late 1980s, however the Brazilian nannoplankton biostratigraphic framework reached a higher resolution in the last thirty years, justifying the development of a new study. The successions are composed mainly by siliciclastic rocks coming from cutting samples and short intervals of cored samples. Eleven biozones were recognized, within the upper Albian and Maastrichtian interval, the biostratigraphic analyses provided a higher resolution mainly for Turonian and Campanian strata in the basin. Absolute and relative abundances of some Cretaceous calcareous nannofossils species provided paleoecological proxies, pioneer in Pelotas Basin using this fossil group. The results suggest a prevalence of warm-water condition, with cooling events during the upper Turonian, upper Turonian/lower Coniacian, upper Coniacian and upper Santonian/lower Campanian.
Keywords: Nanofósseis calcários; Cretáceo; Bacia de Pelotas; Bioestratigrafia; Paleoecologia; Calcareous nannofossils; Cretaceous; Pelotas basin; Biostratigraphy; Paleoecology; ACCNPQ::Ciências Exatas e da Terra::Geologia